2022
DOI: 10.21203/rs.3.rs-2112556/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 pandemic in a mental health ward: inpatient admissions, use of mechanical restraint and aggressions

Abstract: Background. To analyze the impact of the COVID-19 pandemic on mental health hospital admissions, the use of mechanical restraint and number of aggressions to the staff. Methods. Outcomes in the period from March 14, 2020–December 31, 2020 were compared to the same period in 2019. A multivariate logistic regression analysis was carried out to compare the risk of mechanical restraint during admissions in the two periods, controlling for potential confounding variables. Results. There was a 30.7% reduction in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, it is currently unknown whether R/S intervention use changed in other clinical settings, such as EDs, which saw dramatic changes in service provision during the pandemic [4,[10][11][12]. Similarly, existing research has focused solely on R/S use for patients with MH issues [33][34][35][36][37][38][39][40][41], despite the fact that SU-related concerns increased on par with MH-related concerns during the pandemic [19][20][21][22][23][24][25][26] and are a known risk factor for the use of R/S interventions [42,43].…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is currently unknown whether R/S intervention use changed in other clinical settings, such as EDs, which saw dramatic changes in service provision during the pandemic [4,[10][11][12]. Similarly, existing research has focused solely on R/S use for patients with MH issues [33][34][35][36][37][38][39][40][41], despite the fact that SU-related concerns increased on par with MH-related concerns during the pandemic [19][20][21][22][23][24][25][26] and are a known risk factor for the use of R/S interventions [42,43].…”
Section: Current Studymentioning
confidence: 99%
“…Specifically, reducing bed availability by only 5% resulted in the number of R/S events decreasing by more than 50% over nine months following the onset of the COVID pandemic. On the other hand, research from a mental health hospital in Malaga, Spain, found no change in the likelihood of mechanical restraint [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the declaration of COVID-19 (SARS-CoV-2) as a health emergency in January 2020 and then as a pandemic two months later [27], several authors expressed concerns that mandatory preventive measures, including isolation to minimize the transmission of the virus, may have had an impact on the prevalence of restrictive practices in mental health institutions [28,29]. In this regard, international research shows that the COVID-19 pandemic led to a reduction in the frequency and/or length of psychiatric hospitalizations [30][31][32]. For seclusion and restraint rates, results were mixed; some studies indicated a decrease [33,34], while others an increase [34,36].…”
Section: Introductionmentioning
confidence: 99%